PEMETAAN TIPOLOGI PEMBANGUNAN WILAYAH DI KABUPATEN BOYOLALI MENGGUNAKAN ANALISIS KLASTER UNTUK MENDUKUNG PERENCANAAN BERBASIS DATA - Pramudya Amara Setyaningtyas; Devi Afriyantari Puspa Putri (LPPM Universitas Abdurrab, 2026)
Equitable regional development requires policies that match the characteristics of each region; however, to date there has been no comprehensive mapping that quantitatively classifies regional typologies in Boyolali Regency. This study aims to apply cluster analysis to map regional development typologies across 267 villages in 22 sub-districts of Boyolali Regency. Annual demographic data sourced from the Central Statistics Agency (BPS) were processed through data cleaning, feature engineering, and standardization, then modeled using the K-Means clustering algorithm. The optimal number of clusters was determined using the elbow method, and the quality of the results was evaluated using the Silhouette Score. The results show four regional typologies with a silhouette score of 0.2116: Perkotaan Mapan (78 villages), Perdesaan Luas Agraris (52 villages), Desa Berkembang (76 villages), and Desa Taat Pajak (61 villages). The mapping results were implemented as a website-based information system in the form of an interactive map displaying the cluster distribution of each village. User Acceptance Testing (UAT) with 13 prospective users obtained a score of 71.21%, categorized as Feasible. This system can serve as a strategic tool for local governments in formulating more targeted development policies tailored to the specific needs of each region.